Identification of a Novel Pattern Recognition Receptor DM9 Domain Containing Protein 4 as a Marker for Pro-Hemocyte of Pacific Oyster Crassostrea gigas - Jia, Zhihao; Jiang, Shuai; Wang, Mengqiang; Wang, Xiudan; Liu, Yu; Lv, Zhao; Song, Xiaorui; Li, Yiqun; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2021)
DM9 refers to an uncharacterized protein domain that originally discovered in Drosophila melanogaster. Two proteins with DM9 repeats have recently been identified in the Pacific oyster Crassostrea gigas as mannose-specific binding receptors. In the present study, a novel DM9 domain containing protein (designated as CgDM9CP-4) with two tandem DM9 domains was identified from C. gigas. The mRNA expression level of CgDM9CP-4 was highly enriched in hemocytes and gill tissue. After LPS, PGN and Vibrio splendidus stimulations, the expression levels of CgDM9CP-4 in hemocytes were all down-regulated. The recombinant protein of CgDM9CP-4 (rCgDM9CP-4) displayed a broad binding spectrum towards various PAMPs (LPS, PGN, β-glucan, and Mannose) and microorganisms (Staphylococcus aureus, Micrococcus luteus, V. splendidus, Vibro anguillarum, Escherichia coli, Pichia pastoris, and Yarrowia lipolytica). Immunohistochemistry revealed that CgDM9CP-4 was mostly expressed in gills and some hemocytes. Flow cytometry analysis demonstrated that the CgDM9CP-4-positive hemocytes, which accounted for 7.3% of the total hemocytes, were small in size and displayed less granularity. CgDM9CP-4 was also highly expressed in non-phagocytes (~82% of total hemocytes). Intracellular ROS levels and the expression levels of cytokines in CgDM9CP-4-positive hemocytes were much lower than that of CgDM9CP-4-negtive hemocytes. The mRNA expression levels of CgDM9CP-4 in hemocytes were decreased after RNAi of hematopoietic-related factors (CgGATA, CgRunt, CgSCL and CgNotch). In addition, CgDM9CP-4-positive cells were found to be more abundant in hemocytes from gills than those from hemolymph, with most of them located in the gill filament. These results suggest that CgDM9CP-4 is a novel member of PRR expressed in undifferentiated pro-hemocytes to mediate pro-hemocyte maturation in response to stimulation.